ПРИМЕНЕНИЕ МЕТОДОВ СЕЙСМОТОМОГРАФИИ ДЛЯ РЕШЕНИЯ РАЗЛИЧНЫХ ЗАДАЧ В ГОРНО-ГЕОЛОГИЧЕСКОМ НАПРАВЛЕНИИ - Sadchikov, A.; Zhelaeva, N.; Tokusheva, J.; Ponomareva, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Karaganda coal basin is characterized by a complex structure. The presence of geological inconsistencies such as tectonic disturbances, washouts, variable reservoir hypsometry, etc. makes it difficult to conduct underground mining operations. Currently, in the world practice, mine seismic exploration is widely used for the purpose of studying the geological structure and solving various mining problems. Safe and productive operation of treatment faces in underground coal mining requires a timely and reliable forecast of the mining and geological conditions of the structure and condition of the coal-bearing mass from the mine workings. The most accurate and reliable picture of the tectonic structure of the Carboniferous massif can be obtained using methods of mine seismic exploration to study the geological structure and conditions of the coal bed and host rocks. The main goal of implementing modern methods of mine seismic exploration was to conduct mathematical modeling to assess the possibility of identifying tectonic disturbances with an offset amplitude of the order of magnitude and higher than the reservoir capacity using various methods of underground seismic exploration - the seismic transmission method (STM) and the reflected wave method (RWM). For this purpose, physical models of sections of the Carboniferous massif were developed, including a geometric description of geological structures, the distribution of rock densities, velocities, wave propagation and their influence on compression, and the shift of the mountain range. One of the models corresponded to a section of the formation without geological disturbances, and the second one - to a section with tectonic disturbances with displacement amplitudes from 5 to 15 m. The results obtained can be used in the development of modern effective methods for predicting the state of the mountain range in complex mining and geological conditions of both the Karaganda coal basin and other coal basins with a complex geological structure. Initially, seismic surveys were performed using the method of reflected waves using the common depth point method. However, the problem of obtaining an objective image of the geological environment is still relevant, due to the peculiarities of elastic wave excitation in mine conditions (features of the generated wave field, patterns of its propagation, the direction of the source). The method of mine seismic survey based on channel and boundary waves registration was developed and applied. This method allows obtaining a detailed geological and geophysical model of the field site. Due to the processing of both types of waves, the resolution of the method is increased to obtain information about both the coal bed and the host rocks, and, in particular, the state of the roof of the formation. The method of measurements in mine conditions is presented, the results of testing the method of performing field work in mine conditions are shown, and seismic characteristics with high contrast and clear traceability of reflecting boundaries are obtained.
Keywords: Karaganda coal basin; tectonic disturbances; mine seismic survey; source orientation; transverse waves; channel and boundary waves